PENGARUH DOA TERHADAP KUALITAS HIDUP LANSIA DI KOMUNITAS LANSIA DUKUH JOHO, CONDONG CATUR, DEPOK, SLEMAN, YOGYAKARTA - , TULUS TRI PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The number of population and life expectancy of the elderly increase in line with the advancement of health service and medical intervention. Thus it is important to give more attention to efforts of improving the quality of life of the elderly. One of the efforts is spiritual approach through religious activities, i.e. prayer. Objective: The study aimed to identify the influence of prayer to quality of life of the elderly community at Joho, Condong Catur, Subdistrict of Depok, District of Sleman, Yogyakarta Special Territory. Method: The study was a quasi - experiment (one-group pre-posttest design), involving 20 elderly population, members of elderly community at Joho, Condong Catur, Depok, Sleman. Data were obtained through interview and questionnaire of World Health Organization Quality of Life-BREF (WHOQOL-BREF). Quantitative analysis used paired t-test and Wilcoxon. Result: There was significant difference between quality of life of the elderly before and after the practice of praying (p=0.001). There was significant difference in every quality of life domain, physical domain (p=0.001), psychological domain (p=0.016), social domain (p=0.001) and environmental domain (p=0.001). Conclusion: Prayer had significant influence to quality of life of the elderly at the elderly community of Joho, Condong Catur, Subdistrict of Depok, District of Sleman, Yogyakarta Special Territory.